ANALISIS LAPORAN KEUANGAN PADA PT. KIMIA FARMA, TBK PERIODE TAHUN 2016 - 2018 - Desyria Pratiwi (BALANCING: Accountancy Journal, 2021)
Analysis of the company's financial statements is very useful for users of financial statements, so they can find out the development and financial performance of the company. One of the measuring tools for financial statement analysis is using financial ratio analysis. The purpose of this study is to analyze the financial statements of PT. Kimia Farma, Tbk in the period 2016 - 2018. This study uses secondary data sourced from company financial reports, while the author's financial report data is obtained from the official website of the Indonesia Stock Exchange (IDX). The results of data processing that have been done indicate the financial performance of PT. Kimia Farma, Tbk which is seen from the average value of the liquidity ratio shows a fairly good condition, because the average value is above the industry average standard. When viewed from the average value of the financial performance leverage ratio of PT. Kimia Farma is also in quite good condition, because it is indicated by its average value which is below the average value of the industry standard, in other words the company is able to meet its long-term obligations. The average value of the company's activity ratio shows a bad condition because the company has not been able to achieve the predetermined target.